TINJAUAN KEMAMPUAN TEKNIK DASAR SEPAKBOLA SISWA SMP NEGERI 4 KOTA PEKANBARU - Trio Nanda Putra; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research was low achievement in football which was effected by the base technique of passing controlling, dribbling, and shooting which have by the football extracuriculler`s student of SMPN 4 Pekanbaru. The objective of this research was to know the ability of the extracuriculer student of SMPN 4 Pekanbaruin their base technique (passing controlling, dribbling, shooting). The population of this research was 25 students of SMPN 4 Pekanbaru that joined the extracuriculer in football. To collect the data / sample the researcher used total sampling technique,which all of the population were the sample the obtained data data was analyzed with percentage technique. The result showed us that : 1) the ability of students of SMPN 4 Pekanbaru in passing controlling was in the less / low level with only 15 students gained 60%. 2) the ability of the students of SMPN 4 Pekanbaru in dribbling was in low level with only 13 students gained 52%. 3) the ability of the students of SMPN 4 Pekanbaru in shooting was in the average level with only 13 students gained 76%. 4) the ability of the students of SMPN 4 Pekanbaru in the base technique was in the average level with 24 students gained 96%.Keywords: Base technique football